In vitro evaluation of the immunomodulatory and wakame assimilation properties of Lactiplantibacillus plantarum strains from swine milk - Ohgi, Ryusuke; Saha, Sudeb; Zhou, Binghui; Sakuma, Taiga; Sakurai, Mitsuki; Nakano, Yuhka; Namai, Fu; Ikeda-Ohtsubo, Wakako; Suda, Yoshihito; Nishiyama, Keita; Villena, Julio; Kitazawa, Haruki (Frontiers in Microbiology, 2024)
The emergence and spread of antibiotic resistance threat forced to explore alternative strategies for improving the resistance to pathogens in livestock production. Probiotic lactic acid bacteria represent an alternative for this objective. In this study, seven Lactiplantibacillus plantarum strains from porcine colostrum and milk were isolated, identified and characterized in terms of their abilities to modulate immunity in porcine intestinal epithelial (PIE) cells. Then, two potential immunoregulatory strains were studied in terms of their ability to utilize and grow in wakame (Undaria pinnafida). Isolates were identified by16S rRNA gene and evaluated by studying their interaction with PIE cells. The expressions of peptidoglycan recognition proteins (PGRPs), nucleotide-binding oligomerization domain (NODs), host defense peptides (pBD) and type I interferons (IFNs) were evaluated by RT-qPCR. The strain 4M4417 showed a remarkable capacity to differentially regulate the expression of PGRP1, PGRP3, NOD1, NOD2 and pBD1 in PIE cells. On the other hand, the strain 4M4326 was the most efficient to improve the expression of IFN-α and IFN-β in PIE cells challenged with poly(I:C). Both L. plantarum 4M4326 and 4M4417 were characterized in terms of their ability to utilize wakame. Results demonstrated that both strains efficiently grew in wakame-based broth. Our results suggest that L. planatrum 4M4326 and 4M4417 are interesting candidates to develop immunomodulatory feeds based on wakame utilization. These new immunosynbiotic feeds could help to reduce severity of intestinal infections and improve immune health status in pigs.